Struktur Togas Persaingan dan Kerjasama dalam Proses Kumpulan dan lmplikasi Terhadap Amalan Pendidikan - Othman, Ghazali (Penerbit Universiti Sains Malaysia, 1986)
This paper attempts to examine the concept of competitive and cooperative task structure in process and its implications for educational practice. Cooperation and competition are basic processes of social life which have important consequence for diverse aspects of group behavior. Competition theorists postulated that differential rewarding encourages maximum group productivity. This paper also discuss the relationship between the competitive and cooperative task structure and school performance. Several studies on the issue of productivity were cited. Prominent studies ih the differential effects of competitive and cooperative task outcome structure in group process of the school were also examined. Inferences implications for socially heterogeneous classroom and Malaysian Educational settings were also discessed.